Pengaruh NPF, CAR, BOPO, Inflasi dan BI Rate terhadap Profitabilitas (ROA) Pada Bank BCA Syariah Tahun 2015-2022 - Wiwin Koni; Anggi Hasan (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to (1) determine the effect of NPF on ROA of BCA Syariah Bank 2015-2022, (2) to determine the effect of CAR on ROA of BCA Syariah Bank 2015-2022, (3) to determine the effect of BOPO on BCA Syariah Bank ROA 2015-2022, (4) to determine the effect of inflation on BCA Syariah Bank ROA 2015-2022, (5) to determine the effect of the BI Rate on BCA Syariah Bank ROA 2015-2022. (6) to find out whether NPF, CAR, BOPO, Inflation and BI Rate have an effect on BCA Syariah Bank ROA 2015-2022. This research is a type of quantitative research using a descriptive statistical approach. The sampling technique in this research uses a saturated sampling technique where the entire population is used as the sample. The sample in this research is the 32 quarterly financial reports of BCA Syariah Bank for 2015-2022. The type of data in this research is secondary data obtained from www. bcasyariah.co.id in the form of quarterly financial reports, www.bi.go.id in the form of inflation data and www.bps.go.id in the form of BI Rate data. The data analysis technique used is the Multiple Linear Regression data analysis technique using the Eviews 10 application tool. The results of this research show that NPF and BOPO have a significant effect on the ROA of Bank BCA Syariah in 2015-2022, while CAR, Inflation and BI Rate do not have a significant effect on ROA of Bank BCA Syariah in 2015-2022. However, simultaneously NPF, CAR, BOPO, Inflation and BI Rate influence BCA Syariah Bank's ROA for 2015-2022 by 60.3442% and the remainder is influenced by other variables outside the research.